Verteilt und doch verbunden: Virtuelle Teamarbeit - Kauffeld, Simone; Handke, Lisa; Straube, Julia (Gruppe. Interaktion. Organisation., 2016)
This article provides an overview of the current research on the topic virtual teamwork. Despite all the advantages (cost savings, increased flexibility etc.), this form of cooperation is confronted with a number of challenges. Since it is accompanied by a more difficult exchange of information, it represents a source for conflicts and loss of trust. This can severely impair performance and satisfaction within the team. Aside from pointing out potential challenges of virtual teamwork, research-based recommendations on preventing and handling these problems are also demonstrated.
CRIS-Team Scopus Importer:2023-09-18
Keywords: Communication; Competency; Digitalization; Team work; Virtuality